Penyuluhan Kesehatan Reproduksi: Fokus Pada Perdarahan Abnormal Dalam Kehamilan Di Komunitas Pedesaan - Saputri, Nurul Aini Suria; Idrus, Maghfira; Manay, Rahma H. (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Abnormal bleeding during pregnancy is a major cause of maternal morbidity and mortality, particularly in rural areas with limited access to health facilities. This outreach program aims to increase public knowledge and awareness, particularly of pregnant women and their families, regarding the types of bleeding during pregnancy, danger signs, first aid measures, and prevention of further complications. The program implemented an educational approach, interactive discussions, and the distribution of educational media to the community in Lembangloe Village, South Sulawesi. The results showed an increase in participants' understanding of abnormal bleeding and increased family preparedness for pregnancy emergencies. This activity is expected to be the first step in reducing the number of pregnancy complications in remote areas.